Progress in synthesis of ferroelectric ceramic materials via high-energy mechanochemical technique - Kong, Ling Bing (2012)
Ferroelectric ceramics are important electronic materials that have found a wide range of industrial and commercial applications, such as high-dielectric constant capacitors, piezoelectric sonar or ultrasonic transducers, pyroelectric security sensors, medical diagnostic transducers, electro-optical light valves, and ultrasonic motors, to name a few. The performances of ferroelectrics are closely related to the ways they are processed. The conventional solid state reaction method requires high calcination and sintering temperatures, resulting in the loss of lead, bismuth or lithium components due to their high volatilities, thus worsening the microstructural and subsequently the electrical properties of the ferroelectric materials. Various wet chemistry based routes have been developed to synthesize ultra-fine and even nano-sized ferroelectric powders. However, most of the chemistry based routes still involve calcinations, although at relatively lower temperatures. High energy mechanochemical milling process has shown that some ferroelectric materials can be synthesized directly from their oxide precursors in the form of nano-sized powders, without the need for the calcination at intermediate temperatures, thus making the process very simple. A large number of ferroelectric materials, including lead-containing ferroelectrics, antiferroelectrics and relaxors, and bismuth-containing Aurivillius families, have been synthesized by the high-energy milling process. Some ferroelectrics, such as barium titanate (BaTiO3 or BT), lead iron tungstate [Pb(Fe2/3W1/3)O3 or PFW], and several bismuth-containing materials, that cannot be directly produced from their oxide mixtures, have been formed at relatively low temperatures. Ferroelectric ceramics derived from the activated precursors demonstrated better microstructure and electrical properties than those without mechanochemical treatment. This review presents an overview of the recent progress in the synthesis of ferroelectric ceramic powders using various high-energy milling techniques. The progress includes several aspects: (i) direct synthesis of nano-sized powders with better sinterability, (ii) promoted reactive sintering due to the modification of the precursors, (iii) amorphization of the precursors, and (iv) refinement of the precursors with high homogeneity. The underlying mechanisms of mechanochemical synthesis of ferroelectric materials are discussed. Further research emphasises on issues related to the synthesis of ferroelectric ceramic powders are suggested.